First time adoption of IFRS 15 “Revenue from contracts with customers“: the case of Lithuanian listed companies - Vaicekauskas, Darius (Buhalterinės apskaitos teorija ir praktika, 2020)
Revenue accounting is one of the most important areas of financial accounting. Revenue is one of the key absolute financial ratios that reflects the economic benefits generated by entities that result in increased shareholders‘ equity. This article investigates the first time adoption of new IFRS 15 “Revenue from contracts with customers“ which in International financial reporting standards (hereinafter – IFRS) system is mandatory to apply starting from 1 January 2018. The new IFRS 15 supersedes the previous international accounting standards regulating revenue recognition and introduces a conceptual 5-step revenue recognition model. The purpose of this article is to evaluate the impact of the first-time adoption of IFRS 15 “Revenue from contracts with customers“ on the financial statements of Lithuanian listed companies. This purpose is achieved while using the following research methods: analysis of International financial reporting standards (IFRS) and scientific literature, as well as analysis of the content of financial statements. An empirical study revealed that the first-time adoption of IFRS 15 had no material impact on the financial statements of Lithuanian listed companies. Most of the companies surveyed applied the standard using a simplified retrospective modified method and did not pay much attention to the disclosure of first-time adoption. For those affected by the standard, the effect was mostly notable in the following areas: reclassifications of commissions and brokerage fees, changes in revenue recognition principles from the revenue recognition over a time to revenue recognition at specific point in time and vice versa.